Hemostatic activity of aqueous extract of Myrtus communis L. leaf in topical formulation: In vivo and in vitro evaluations. (1st March 2020) - Ebrahimi, Fatemeh; Mahmoudi, Javad; Torbati, Mohammadali; Karimi, Pouran; Valizadeh, Hadi
Abstract: Ethnopharmacological relevance: Myrtus communis L. (MC) is a well-known medicinal plant in traditional Persian medicine, which contains a large amount of phenolic compounds (mainly hydrolyzable tannins). As mentioned in ancient literature, MC was widely used to control bleeding in every part of the body. Nevertheless, there is no pharmacological study on the anti-hemorrhagic activity of this plant till now. Aim of the study: The current in vivo and in vitro study aimed at evaluating the hemostatic activity of M. communis aqueous leaf extract (MCE) in topical formulation. Materials and methods: Two parameters of bleeding time and amount in tail bleeding model were measured in vivo in rats treated with MCE (1%, 2.5%, 5%, 7.5%, 10%, 15%, and 20% w/v), 5% M. communis aqueous leaf extract gel (G), tannic acid (TA) (1%, 2.5%, 5%, 7.5%, and 10%), normal saline (NS), and the Monsel's solution (MS), a commercial hemostatic agent. Also, the effect of 5% MCE and 5% TA on PT (prothrombin time) and aPTT (activated partial thromboplastin time) as well as protein precipitation and platelet aggregation were assessed in vitro . Results: In the rat-tail bleeding model, bleeding time and amount significantly (P < 0.001) reduced by the application of 5% MCE solution on the cut tail compared with the NS group. The bleeding time and amount in the MS group were not significantly different from those of the 5% MCE group. Platelet microaggregates were detected by fluorescent microscope. PT and aPTT values increased >120 s and >180 s by 5% MCE, respectively. Also, protein precipitation and significant reduction in serum proteins were observed in the 5% MCE group. Conclusion: The current study provided new insights into the hemostatic effect of MCE, which may be partially mediated by platelet aggregation activity. Hence, it could be evaluated as the resource of new plant origin hemostatic agent. Graphical abstract: Image 1